Internal Audit and Administrative management of the administrative workers of the National University of Concepción, year 2023 (Revista Científica UCOM Scientia, 2025)
At the National University of Concepción (UNC), internal audit and administration have worked independently from the beginning, focusing on control processes. Taking into account that many studies suggest that internal audit should go hand in hand with administration, although it is understood that it is not a direct responsibility, the processes included in both sectors generate an advisory and mutual support function, evaluating and strengthening in a timely and proactive manner the different processes or situations that may arise during the development of activities. For this reason, the research was developed with the objective of analyzing the relationship between internal audit and the administrative management of the administrative officials of the UNC, in the year 2023. Likewise, the research methodology was correlational, with a non-experimental and cross-sectional design, with a quantitative approach. The population consisted of 223 administrative officials, and the sample of 145 officials was determined using the finite population formula. A survey technique was used to collect data: the Internal Audit Questionnaire, which considered the three dimensions of auditing (planning, techniques, and evaluation), and the Administrative Management Questionnaire, which considers the four dimensions of administration (planning, organization, direction, and control). Furthermore, the main hypothesis was the existence of a relationship between internal auditing and administrative management; and to analyze the correlation between variables, the SPSS statistical program was used to determine the Pearson correlation coefficient. In this way, the result was obtained that audit planning has a high positive relationship with planning (sig.=0.000 and r=0.645) and organization (sig.=0.000 and r=0.670), while with management (sig.=0.000 and r=0.532) and control (sig.=0.000 and r=0.452), a moderate positive relationship was found; similar result in terms of audit techniques, since a high positive relationship was also found with planning (sig.=0.000 and r=0.726) and organization (sig.=0.000 and r=0.630), and a moderate positive relationship with management (sig.=0.000 and r=0.589) and control (sig.=0.000 and r=0.458), and finally, in terms of audit evaluation, like the other dimensions, it resulted in a high positive relationship with planning (sig.=0.000 and r=0.667) and organization (sig.=0.000 and r=0.693), and a moderate positive relationship with management (sig.=0.000 and r=0.565) and control (sig.=0.000 and r=0.544). Finally, a relationship between the two variables was established, with a significance level of 0.000 and a very high positive correlation of r = 0.817. This means that the higher the level of Internal Audit, the higher the level of Administrative Management. Based on these results, we can aim for stronger and more integrated collaborative work, enabling both areas to leverage each other for decision-making aimed at institutional strengthening.